Artificial blood feeding for Culicidae colony maintenance in laboratories: does the blood source condition matter? - Dias, Luciana dos Santos; Bauzeruzer, Luíz Guilherme Soares da Rocha; Lima, José Bento Pereira (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Culicidae colonization in laboratory is paramount to conduct studies aiming at a better understanding of mosquitoes’ capacity to transmit pathogens that cause deadly diseases. Colonization requires female blood feeding, a necessary step for maturation of female’s oocytes. Direct blood feeding on anesthetized mammals implies in a number of disadvantages when compared to artificial blood feeding. Consequently, laboratories worldwide have been trying to -feed female mosquitoes artificially in order to replace direct feeding. In this study, we compared the effects of direct blood feeding and artificial blood feeding on important life traits of three Culicidae species. Artificial feeding was performed using citrated or defibrinated sheep blood and citrated or defibrinated rabbit blood. Direct feeding was performed using anesthetized guinea pigs as the blood source and the experiment control. Results indicated that artificial feeding using sheep blood was not good enough to justify its use in the maintenance of laboratory colonies of Culicidae. However, artificial feeding using rabbit blood maintained a recovery rate always very close to the control, especially when blood was citrated. We concluded that artificial feeding using citrated rabbit blood can substitute direct feeding on mammals reducing the use of animals, eliminating the need to maintain a bioterium in the laboratory and reducing costs in scientific researches involving Culicidae vectors.